2022
DOI: 10.3390/jox12040019
|View full text |Cite
|
Sign up to set email alerts
|

Narrative Review: Glucocorticoids in Alcoholic Hepatitis—Benefits, Side Effects, and Mechanisms

Abstract: Alcoholic hepatitis is a major health and economic burden worldwide. Glucocorticoids (GCs) are the only first-line drugs recommended to treat severe alcoholic hepatitis (sAH), with limited short-term efficacy and significant side effects. In this review, I summarize the major benefits and side effects of GC therapy in sAH and the potential underlying mechanisms. The review of the literature and data mining clearly indicate that the hepatic signaling of glucocorticoid receptor (GR) is markedly impaired in sAH p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 243 publications
0
10
0
Order By: Relevance
“…This study was performed to understand the GR's effect on chemokine and APP expression in the liver. We hypothesized that by increasing GR activity in the liver, chemokine imbalances seen in diseases such as AH [71] could be ameliorated, thus treating or preventing the development of sepsis in this high-risk patient group [9]. To summarize our findings, GR's effect on chemokine expression is more complicated than a simple anti-inflammatory inhibition.…”
Section: Discussionmentioning
confidence: 90%
“…This study was performed to understand the GR's effect on chemokine and APP expression in the liver. We hypothesized that by increasing GR activity in the liver, chemokine imbalances seen in diseases such as AH [71] could be ameliorated, thus treating or preventing the development of sepsis in this high-risk patient group [9]. To summarize our findings, GR's effect on chemokine expression is more complicated than a simple anti-inflammatory inhibition.…”
Section: Discussionmentioning
confidence: 90%
“…We found that Foxo3 mRNA was down-regulated by ethanol in the WT AS mice (data not shown), which may contribute to the trend of down-regulation of GILZ in WT AS mice. In contrast to the activation of GR in acute AS, hepatic expression of GR and GR-target genes are markedly down-regulated in sAH patients (Lu, 2022). Further study on the mechanism of hepatic GR deficiency in sAH is warranted.…”
Section: Discussionmentioning
confidence: 99%
“…Marked steatohepatitis, jaundice, cholestatic liver injury, and impaired liver regeneration are hallmarks of sAH which causes high mortality (Sidhu et al, 2017, Hosseini et al, 2019). Literature suggests hepatic GR deficiency in fatty liver and AH (Ahmed et al, 2012, Nasiri et al, 2015, Lu, 2022). Most recent literature support a protective role of hepatocellular GR against steatosis during high fatty acid influx (Nasiri et al, 2015, Roqueta-Rivera et al, 2016, Quagliarini et al, 2019, Lu et al, 2022, Mueller et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Patients with alcoholic hepatitis (AH) have severe inflammation and cholestatic liver injury [ 2 ], and severe AH (sAH) has a high mortality rate [ 3 ]. Glucocorticoids (GCs) are currently the only available drug therapy for sAH [ 4 ], however, prednisolone, the current standard of care for sAH, only marginally reduces 28-day mortality without long-term improvement [ 5 ]. Additionally, sepsis is a leading cause of death of sAH [ 6 , 7 ], and hepatic GR is essential to protect against liver failure and mortality in sepsis [ 8 ].…”
Section: Introductionmentioning
confidence: 99%